Effects of vertical shear on intensification of tropical cyclones of different initial sizes - Bi, Mingyu; Wang, Ruifang; Li, Tim; Ge, Xuyang (Frontiers in Earth Science, 2023)
Idealized experiments were conducted to examine the impacts of moderate vertical wind shear (VWS, i.e., magnitude of 12 m s−1) on the intensification of tropical cyclones (TCs) of different initial sizes. The results showed that the intensity of all the simulated TCs decreased at the first 12-hour integration after imposing the shear. Larger TCs resumed intensification earlier, whereas smaller ones re-intensified more slowly or even failed to intensify. The differences in the intensification rate are likely due to the tilting magnitude. Under VWS, the upper-level TC center exhibited a horizontal displacement relative to the low-level circulation. In general, this displacement was smaller in larger TCs, indicating that larger TCs are less susceptible to VWS. Thermodynamically, the intrusion of mid-level low moist entropy also played a role in suppressing upshear convection. This negative impact was pronounced in smaller TCs. By using the PV-ω equation, the resilience of TC to VWS was compared. The second circulation forced by both dry dynamic and diabatic heating acted to restore the system to a vertically upright position. For larger TCs, more extensive convection was prolific on the downshear side, and its corresponding forced second circulation offset a larger part of the low-to mid-level environmental shear, which made larger TCs more resilient to VWS; i.e., larger TCs produced stronger low to middle counter shear circulation and facilitated vertical realignment. In contrast, for smaller TCs, the updrafts forced by dry dynamic and diabatic heating were deeper but narrower at the initial time, which did not efficiently reduce the mid-level VWS, resulting in greater tilting of the TC, thus making the smaller TCs more vulnerable to VWS.